Assessment and Analysis of Agriculture Technology Adoption and Yield Gaps in Wheat Production in Sub-Tropical Punjab - Singh, Gurdeep; Singh, Pritpal; Sodhi , G. P. S. (Indian Journal of Extension Education, 2017)
Yield gap analysis evaluates magnitude and variability of difference between crop yield potential and yield obtained at  farmers' fields. The magnitude of yield gap and related causes vary substantially, and depends upon technology gap  generated by partial or incomplete adoption of locally optimized technology. Periodic survey (2013-16) revealed that ~6- 22 per cent of wheat area in Mansa (Punjab)during 2012-16 was under un-recommended varieties. More than 1/3rd  (~35%) of farmers were using un-treated wheat seed and therefore, experienced infestation of seed borne diseases at their  -1 fields. About 28 per cent farmers were using higher seed rate than recommended (100 kg seed ha ), constitutes majority of  th those farmers who had retained seed from previous year harvest. Only 1/10 of farmers apply fertilizer N to wheat at  -1 recommended rate (125 kg N ha ). About 81 per cent farmers did not apply basal N dose, therefore, appearance of N  deficiency on lower wheat leaves occur commonly, resulting in a significant set-back on crop grain yield. Data revealed  that 91, 79 and 67 per cent of farmers did not apply K, Zn and Mn, respectively to wheat, albeit of their deficiency in the  -1 soils. An assessment of yield gap showed a potential to increase the wheat grain yield upto 0.91t ha .Seed treatment before  -1 sowing resulted in an increase in wheat grain yield by 0.30 t ha (6.1 %). Nitrogen application at sowing increased wheat  -1 grain yield by 0.62 t ha (13.6 %), compared with plots without basal N application. Results of the survey showed a  -1 potential to increase wheat grain yield from 0.28-1.08 t ha (6.5-25.6 %) with foliar application of MnSO4.Therefore,  understanding crop yield potentials and exploitable gaps in crop production is essential to increase grain yield.
Keywords: Technology gap; nutrient management; varietal evaluation; wheat production; yield gap